Gambaran Efektivitas Spanduk Sebagai Media Komunikasi Kesehatan di Desa Oemasi - Afrona Elisabeth Lelan Takaeb (Universitas Nusa Cendana, 2019)
Billboard is an outdoor health communication media aimed to promote health behavior in large audience. This research objective was to describe the effectiveness of billboards in the Oemasi Village Office in terms of visibility, size, and visual design. Descriptive design was applied and 43 respondents were selected by using a convenience sampling technique. Research showed that only 32 respondents (74%) had seen the billboard while the rest, 11 respondents (26%) had not. From 32 respondents, only 27 respondents (84%) had read the message written in while the rest, 5 respondents (16%) had not. Limitations of this media reported were related to the inadequate placement of this media in Village Office as it is rarely visited, the small size of the media leading to the lack of its visibility both picture and written text in reaching the attention of respondents. Therefore, the improvement of size and color is necessary as well as this media to be placed in some selected points in the village to have more attention from the community.